Retrospective Analysis of Diabetic Admissions: Moving Forward by Looking Back - Mathur, Gagan; Mathur, Shuchi; Prakash, Prabhu; Agarwal, Harish; Mathur, Shyam; Mathur, Arvind; Kackar, Mohit; Saini, Dinesh Kumar (National Journal of Community Medicine, 2013)
Background: Diabetes Mellitus is an “iceberg” disease. Developing countries are experiencing a dramatic increase in prevalence of Diabetes Mellitus. Studying pattern and outcome of diabetic admissions can be helpful in determining the effectiveness of inpatient and outpatient care. Objective: Diabetes related admissions to medical and surgical wards of a Tertiary Care Center at Jodhpur were retrospectively studied, with an aim to determine the burden that diabetes poses on the health care system. Changes and improvements in both inpatient and outpatient management of diabetes can be made by analyzing the data collected. Methods: A one year retrospective, hospital based, clinical study was carried out at M.D.M. hospital, Jodhpur, Rajasthan, India. Medical records of the diabetic patients admitted to the medical and surgical wards, between April 2010 and March 2011 were studied and the data collected was analyzed. Results: During the study period a total 9,320 patients were admitted to medical and surgical wards, out of which 411(4.41%) admissions were diabetes related. The mean age of the patients was 54.51+/-17.12 years (range, 10-90 years). Reasons for admissions were Infections/septicemia (24.57%), Hyperglycemic Emergencies (15.58%), cardiac disease (13.63%) and, renal disease (6.08%). The common associated medical conditions were Anemia (59.85%) and Hypertension (40.14%). Duration of hospital stay ranged from 1 to 34 days, with a mean duration of 5.36 days. Mean duration of hospital stay was the longest (11.36 days) for those admitted for diabetic foot ulcer. Conclusion: Efforts should focus on establishing clinics having facilities for treatment of all aspects of diabetes, including complications.